2012
DOI: 10.1186/1471-2164-13-311
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Shiga toxin encoding bacteriophages

Abstract: BackgroundStx bacteriophages are responsible for driving the dissemination of Stx toxin genes (stx) across their bacterial host range. Lysogens carrying Stx phages can cause severe, life-threatening disease and Stx toxin is an integral virulence factor. The Stx-bacteriophage vB_EcoP-24B, commonly referred to as Ф24B, is capable of multiply infecting a single bacterial host cell at a high frequency, with secondary infection increasing the rate at which subsequent bacteriophage infections can occur. This is biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 72 publications
6
96
0
Order By: Relevance
“…The model proposed by Gamage et al suggested that a lytic infection of these strains by phage that are spontaneously released by E. coli O157:H7 increases the number of phage particles, as well as Stx2 levels. This model was developed using a single strain of E. coli O157:H7, although stx 2 -bearing phage are known to be highly polymorphic (29)(30)(31). We hypothesized here that strain-specific differences between these phage would impact the level of toxin amplification observed.…”
mentioning
confidence: 99%
“…The model proposed by Gamage et al suggested that a lytic infection of these strains by phage that are spontaneously released by E. coli O157:H7 increases the number of phage particles, as well as Stx2 levels. This model was developed using a single strain of E. coli O157:H7, although stx 2 -bearing phage are known to be highly polymorphic (29)(30)(31). We hypothesized here that strain-specific differences between these phage would impact the level of toxin amplification observed.…”
mentioning
confidence: 99%
“…One distinction that can be made with little ambiguity is that between infections that are productive versus infections that instead display lysogenic cycles, with both infection types at least potentially serving as primary infections, that is, infections of otherwise not phage-infected bacteria. Logically, therefore, the primary infection of a bacterial lysogen can be viewed as a secondary infection of a lysogenic infection, see for example, (Davis et al, 1999;Espeland et al, 2004;Fogg et al, 2007;Mann , 2003;Slavcev and Hayes, 2002;Smith et al, 2012;Weinfeld and Paigen, 1964;Werner and Christensen, 1969;Yamada et al, 2007). One can also describe such secondary infections within this context as superinfections (Sturino and Klaenhammer, 2006) and indeed the term "superinfection" generally appears to be more common within the phage literature than "secondary infection", including within the context of the concept of superinfection immunity as well as that of superinfection exclusion.…”
Section: Parallel Secondary Infection and Its Ambiguitymentioning
confidence: 99%
“…Examples can readily be found in some of the emerging or reemerging pathogens, including heterogeniety of the genes for diphtheria toxin, tox, and its iron-dependent regulator, dtxR, in clinical isolates of Corynebacterium diphtheriae from epidemic outbreaks [71]; production of superantigen variants among group A streptococci [63], exotoxindiversity among community-acquired versus hospital-acquired methicillin-resistant Staphylococcus aureus strain lineages [72]; cholera toxin production by Vibrio cholerae isolates [7,73]; heat-labile enterotoxin (a homologue of cholera toxin) production by enterotoxigenic Escherichia coli strains (ETEC) [74]; and the widespread production of Shiga toxin variants among the Shigella and E. coli strains [75][76][77]. Indeed, studies on Shiga toxin (stx) gene-containing phages indicate that they are transmitted not only by temperate bacteriophages between different bacteria in vivo (i.e., in the intestines of humans and animals [78][79][80]), but also extraintestinally in aquatic environments, such as oceans [81], sewage, and other fecally contaminated water sources [76,82,83], and irrigation water, soil, and crops [84,85].…”
Section: S Rrna-depurinating Toxinsmentioning
confidence: 99%
“…Indeed, it appears that no two sequenced Stx-encoding phages are the same, and indeed, other than the stx genes remaining linked to the λ-like transcriptional activator Q gene, nearly all of the phages are mosaics showing appreciable evidence of genomic recombination and gene-swapping events [77]. The two classes of Shiga toxins found in STEC, Stx1 and Stx2, have similar structures and mechanisms of action.…”
Section: Toxins Encoded By Plasmids Bacteriophages and Other Pathogmentioning
confidence: 99%